Do-it-yourself menu management and pricing - Lai, Hao Bin Jack; Karim, Shahrim (Palgrave Macmillan, 2023)
The restaurant menu requires constant re-evaluation to achieve a balance of proﬁtability and customer satisfaction. A con-structive research approach was taken to identify the challenges and practical requirements of small and micro restaurant practitioners to facilitate menu analysis and revenue management implementation within their establishments. The developed framework does not require any collection of data and guidance, and hence can be easily implemented for businesses of any circumstance. Through observing implementation of the developed framework in small and micro restaurant outlets, this framework was found to be eﬃcient for menu planning, strategizing and expansion, but inappropriate for day-to-day operational usage.